Nurses' and doctors' perceptions regarding the implementation of a triage system in an emergency unit in South Africa - Jean E. Augustyn; Valerie J. Ehlers; Susanna P. Hattingh (AOSIS, 2009)
Triage assessment of patients on arrival at an emergency unit is an essential function in quality emergency care provision, and is a cost-effective and time saving venture. This study investigated nurses' and doctors' perceptions about the implementation of the Cape Triage Score in one emergency unit. The challenges encountered prior to the implementation of the Cape Triage Score and the roles and core competencies of the triage nurse were addressed as well as the strengths and weaknesses of the Cape Triage Score. In this descriptive, quantitative and exploratory study, 15 nurses and doctors completed questionnaires. The challenges decreased and the sorting of patients improved after the implementation of the Cape Triage Score. Other strengths of this system included that the triage nurse prioritised patients, as opposed to the receptionist or the administrative staff; and nurses could undertake preliminary investigations without waiting for doctors' orders to do so. The weaknesses of the implemented Cape Triage Score included that it was not fully functional 100% of the time, and that it was difficult to maintain during peak admission periods due to a shortage of nurses. The recommendations included that management should be convinced of the system's benefits; nurses should perform the triage function on a rotation basis; more nurses should be available during peak periods; and that the administrative and reception staff should also be orientated about the triage system. Opsomming Triage assessering van pasiënte met hulle aankoms by 'n ongeluk/noodeenheid is 'n noodsaaklike funksie van noodsorgvoorsiening, en is 'n koste-effektiewe en tydbesparende onderneming. Hierdie studie het die persepsies van dokters en verpleegkundiges ondersoek betreffende die implementering van die Cape Triage Score in een noodeenheid. Die uitdagings wat ervaar is voor die implementering van die Cape Triage Score, die rolle en kernvaardighede van die triage verpleegkundige asook die swak en sterk punte van die Cape Triage Score is aangespreek. In hierdie beskrywende, kwantitatiewe en verkennende studie het 15 verpleegkundiges en dokters vraelyste voltooi. Uitdagings het verminder en die prioritisering van die pasiënte het verbeter na die implementering van die Cape Triage Score. Ander sterk punte van die stelsel het ingesluit dat die triage verpleegkundige die pasiënte geprioritiseer het, nie die ontvangsdame of die administratiewe personeel nie, en verpleegkundiges kon voorlopige ondersoeke doen sonder om op doktersbevele te wag. Die swakhede van die geïmplementeerde Cape Triage Score het ingesluit dat dit nog nie ten volle 100% van die tyd gefunksioneer het nie, en dat dit moeilik was om triage gedurende spitstye te handhaaf as gevolg van 'n tekort aan verpleegkundiges. Die aanbevelings het ingesluit dat bestuur oortuig moet word van die voordele van die stelsel, verpleegkundiges triage funksies op 'n rotasiebasis moet uitvoer, meer verpleegkundiges beskikbaar moet wees gedurende spitstye; en dat administratiewe en ontvangspersoneel ook georiënteer moet word ten opsigte van die triage stelsel.